Hydrogen- and halogen-bond driven supramolecular architectures from small molecules to cavitands, and applications in energetic materials - Gamekkanda Gamaethige, Janaka Chaminda (Kansas State University, 2018)
A family of six β-diketone based ligands capable of simultaneously acting as halogen-bond (XB) donors (each of para and meta substituted chloro, bromo and iodo functionalities) and chelating ligands was synthesized. Four ligands were characterized by X-ray diffraction to identify the structural behavior of the ligand itself. The free ligands bearing bromine and iodine show XB interactions (C-X···O) whereas the ligand containing chlorine did not show XB interactions. The corresponding Cu(II) complexes for ligands were also synthesized in different solvents such as acetonitrile, ethyl acetate and nitromethane. Both acetonitrile and ethyl acetate participate in XB interactions with XB donors (Br or I) although nitromethane does not participate in such interaction. Metal-ligand complexes with iodine as XB donor in the para position engage in XB interactions to make extended supramolecular architecture when the solvent is nitromethane. When the XB donor attached in the meta position of the ligand, formation of extended supramolecular architecture was seen even in the presence of a strongly coordinating solvent such as acetonitrile. Two tetra functionalized molecules bearing hydrogen-bond (HB) donors (-OH) and XB donors (-C≡C-I) and one tetra functionalized molecule which has only HB donors (-OH and -C≡C-H) were synthesized. The donor molecules themselves show potential for making HB and XB interactions with the available acceptor sites present in the system. The competition between intermolecular HB and XB was explored by co-crystallizing with suitable nitrogen based acceptors. HB and XB donors showed equal competitiveness toward common acceptors when making HB/ XB interactions. Furthermore, the geometry and relative positioning of the donor sites can, in certain cases, change the balance between the competing interactions by favoring HB interactions. A series of cavitands functionalized with XB donors, HB/XB donors and β-diketone have been synthesized. Binding preferences of XB and HB/XB cavitands towards a series of suitable HB/XB acceptors were studied in solid state and they have confirmed the presence of interactions between donor and acceptors. Cavitands with β-diketone functionality were subjected to binding studies with metal ions in solution as well as in the solid state. Successful metal-ligand complexation in solid state as well as in solution state based on UV/Vis titrations have been confirmed. In order to stabilize chemically unstable energetic compound, pentaerythritol tetranitrocarbamate (PETNC), a co-crystallization approach targeting the acidic protons was employed. A co-crystal, a salt and a solvate were obtained and the acceptors were identified as supramolecular protecting groups leading to reduced chemical reactivity and improved stability of PETNC with minimal reduction of desirable energetic properties. Several potential tetrazole based explosives which are thermal and impact sensitive and solid propellants which are impact sensitive were subjected to co-crystallization experiment to stabilize and enhance their properties. Co-crystals and salts of the explosives were obtained with suitable nitrogen based and oxygen based acceptors. The impact sensitivity and thermal instability of the explosives were improved with the introduction of co-formers. Oxygen based acceptors have shown more favorable explosive property improvements compared to nitrogen based acceptors with significant retention of explosive nature of the parent explosives.
Keywords: Crystal engineering; Energetic materials; Hydrogen bonding; Halogen bonding; Host-guest chemistrySupramolecular chemistry